A influência do gênero no lazer: ideologia e práticas - Pereira, Jéssica Bruna Borges (2019)
Leisure is not a disinterested activity, but has social elements that condition it, which leads to understand it as a social practice, as its various forms of manifestation are socially structured and recognized. Here we focus on the determinants of gender, which are social constructions about what it is to be a woman and to be a man, and how they reflect an ideological system that legitimates a power relationship between the two. The study aims to characterize adult attribution of Uberlândia-MG on the division of leisure activities according to gender, their relationship with ideological aspects related to the asymmetrical relations between women and men and to understand how social position can influence such attribution. To that end, 913 adults completed a questionnare, which should characterize 16 leisure activities as being aimed more at women, more at men or at both. Through the analysis of frequencies, multiple correspondence analysis and double-decker plots, it was possible to verify that more gender-related activities reproduce and maintain an ideological logic of gender roles, determining expectations of how men and women are located in the social environment, with women being assigned activities related to motherhood and subordination, whereas men are associated withactivities linked to virility and domination. In addition, younger and more educated people are more favorable to an egalitarian division of activities between genders.